3 mm band line survey toward the high-velocity compact cloud CO−0.40−0.22. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Oka, T.; Tanaka, K.; Matsumura, S.; Miura, K.; Takekawa, S.; Takahata, Y.; Nishino, Akihiko
Abstract: High-velocity compact clouds (HVCCs) are a population of molecular clouds which have compact appearance ( d < 10 pc) and large velocity width (Δ V > 50 km s −1 ), and are found in the central molecular zone of our Galaxy. We performed a 3 mm band line survey toward CO−0.40−0.22, a spatially unresolved HVCC with an extremely large velocity width (Δ V ≃ 90 km s −1 ), using the Mopra 22 m telescope. We surveyed the frequency range between 76 GHz and 116 GHz with a 0.27 MHz frequency resolution. We detect at least 54 lines from 32 molecules. Many line profiles show a prominent peak at vLSR ∼ 70 km s −1 with very large velocity width, indicating they are emitted by the HVCC. Detections of largish molecules are indicative of non-equilibrium chemistry. We extracted some prominent lines based on velocity structure, intensity ratios, and PCA analyses. Shock diagnostic lines (SiO, SO, CH3 OH, HNCO) and dense gas probes (HCN, HCO + ) appear to be prominent. Excitation analysis of CH3 OH lines show an enhancement in T rot in the negative high-velocity end of the profile. These results suggest that CO−0.40−0.22 has experienced a shock, acceleration, compression, and heating in the recent past.